CTNI-38. PAMIPARIB IN COMBINATION WITH RADIATION THERAPY (RT) AND/OR TEMOZOLOMIDE (TMZ) IN PATIENTS WITH NEWLY DIAGNOSED (ND) OR RECURRENT/REFRACTORY (R/R) GLIOBLASTOMA (GBM); PHASE 1B/2 STUDY UPDATE. (9th November 2020) - Piotrowski, Anna; Puduvalli, Vinay; Wen, Patrick; Colman, Howard; Campian, Jian; Pearlman, Michael; Butowski, Nicholas; Cloughesy, Timothy; Battiste, James; Glass, Jon; Schiff, David; van den Bent, Martin; et al.
Abstract: Pamiparib, an investigational, oral PARP 1/2 inhibitor, demonstrated preclinical brain penetration and synergistic cytotoxicity with TMZ. We report updated safety and antitumor data for pamiparib plus RT and/or TMZ in ND-GBM or R/R-GBM (SNO 2019, ACTR-39). This dose-escalation/expansion study includes three arms: A, pamiparib (2, 4, or 6 weeks) plus RT (6–7 weeks) in ND-GBM with unmethylated MGMT promoter (unmethylated-GBM); B, pamiparib (6 weeks) plus RT and increasing TMZ doses in Weeks 1 and 5 of RT in unmethylated ND-GBM; and C, pamiparib plus increasing TMZ doses in methylated/unmethylated R/R-GBM. Most patients in Arms A (expansion) and B received maintenance pamiparib plus TMZ after post-RT rest period at Arm C expansion. As of April 10, 2020, enrollment was complete (N=116; A, n=60; B, n=9; C, n=47). Median study follow-up was 11.3 mo ( A / B ) and 7.1 mo (C ). Common grade ≥3 AEs were anemia (10%) in Arm A; decreased neutrophil and white blood cell count (each 22%) in B; anemia, fatigue, and decreased lymphocyte count (each 11%) in C. Brain edema ( A ) and pneumonia ( C ) (n=1 each) were fatal treatment-unrelated AEs. In ND-GBM, modified disease control rate (DCR following post-RT rest period) was 69.8% (95% CI, 55.7–81.7) overall, 68.8% (50.0–83.9) in A, and 80.0% (28.4–99.5) in B . Median duration of response was 5.1 mo (overall), 3.8 mo ( A ), and NE ( B ). In Arms A / B, median progression-free survival (PFS) and median overall survival (OS) were 4.4 mo and 12.7 mo, respectively; 12-mo OS rate, 54% (95% CI, 40–66). In R/R-GBM ( Arm C ), confirmed ORR was 9.1% (95% CI, 2.5–21.7); median PFS and OS were 1.9 mo and 7.3 mo, respectively; 6-mo PFS rate, 19% (95% CI, 9–32). These results showed a manageable safety profile for pamiparib +/- RT +/-TMZ; response and survival results support further evaluation of these combinations in GBM.